Investigating the Nexus between Law, Environmental Hazards to Life in Pakistan and Environmental Sociology - Dr. Bahadar Ali (Journal of Peace, Development and Communication, 2022)
Environmental problems constitute one of the major concerns in contemporary times such as environmental pollution, climate change, depletion of natural resources and biodiversity loss etc. all of the environmental changes have emerged us with one of the biggest challenges that human beings are confronted with globally. These environmental changes are certainly due to human intervention, in other words we can say that the human induced factors for instance the industrialization, development of modern transport and communication use of modern appliances etc. have led to these environmental deteriorations. There is constant interaction between human beings and the environment; just like the human interaction changes the environment, in the same way the environmental factors play and significant role in shaping social phenomenon. Hence we can say that environmental problems constitute an area of study with in sociology. The study is an attempt to explore the nexus between law, environment and Sociology. It further explains how the environment affects the society and the role of a legal system in coping up the adverse environmental impact on life and society.